Reconstructing Gender-Responsive Restorative Justice for Domestic Violence: A Study of Contextual Islamic Law in Indonesia - Siti Nurlaila; Nunung Rodliyah; Maya Shafira; Rehulina Rehulina; Elfa murdiana (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
Restorative Justice (RJ) has increasingly been institutionalized within Indonesia’s criminal justice system, including in cases of domestic violence (Kekerasan Dalam Rumah Tangga / KDRT). However, its implementation continues to generate serious criticism because it often prioritizes procedural settlement over substantive victim protection. Existing studies largely focus on the effectiveness or normative legality of RJ, while insufficiently addressing the intersection between gender justice, victim vulnerability, and contextual Islamic legal principles. This study fills that gap by reconstructing a gender-responsive RJ framework grounded in contextual Islamic law and maqāṣid al-syarī‘ah. This research employs a normative-empirical socio-legal approach that integrates doctrinal legal analysis with qualitative empirical findings from domestic violence cases in Lampung Province, Indonesia. Data were collected through analysis of legislation, institutional policies, Komnas Perempuan reports, and in-depth interviews with law enforcement officials and related stakeholders. The data were analyzed using a gender-responsive restorative justice framework and contextual Islamic legal interpretation. The findings reveal that the current implementation of RJ in KDRT cases remains predominantly procedural-formalistic. Approximately 72% of victims accepted restorative settlements due to structural pressures, including economic dependence, family coercion, and fear of social stigma, rather than genuine psychological recovery. Furthermore, the absence of mandatory trauma assessment and post-settlement supervision contributed to repeated violence in 40% of the observed cases. This study argues that prevailing interpretations of iṣlāḥ (reconciliation) have been reduced to symbolic peace-making that neglects substantive justice and victim safety. As its principal contribution, this study formulates a three-stage gender-responsive RJ reconstruction model based on contextual Islamic law: (1) a precondition stage requiring psychological assessment and perpetrator accountability; (2) a mediation stage involving gender-sensitive counselors and progressive Islamic law experts; and (3) a post-process stage based on continuous state monitoring and victim protection. The study further demonstrates that integrating contextual Islamic legal values into national law strengthens restorative justice by aligning it with the principles of ḥifẓ al-nafs (protection of life), human dignity (karāmah insāniyyah), and substantive gender justice. This research contributes theoretically to the development of gender-responsive restorative justice discourse within Muslim-majority legal systems and offers a practical policy framework for reforming restorative justice mechanisms in Indonesia and other plural legal societies